Muatan Nilai-nilai Pancasila dalam Serial Animasi Adit dan Sopo Jarwo sebagai Alternatif Media Pembelajaran pada Tema Selamatkan Makhluk Hidup Kelas VI SD - Laili Rizki Wahyuni; Nindya Nurdianasari; Hari Satrijono; Fajar Surya Hutama; Soekma Yeni Astuti (Jurnal Ilmu Pendidikan Sekolah Dasar, 2022)
The purpose of this research is to define the content of Pancasila values in the adit and sopo jarwo animated series and adit and sopo jarwo animation series as an alternative learning media on the theme of Selamatkan Makhluk Hidup class VI elementary school. The method used is documentation that is done using data analysis guidance instruments and interviews using structural interview guidance instruments. The data analysis technique in this study uses an analysis model according to Miles and Huberman (in Sugiyono, 2011:246), that qualitative data analysis consists of data reduction, data presentation, and conclusion withdrawal. There are 3 episodes that will be analyzed, namely the 170th, 183rd and 186th episodes. The results showed that the content of Pancasila values in the adit and sopo jarwo animated series included, godly value 11%, human value of 52%, unity value of 22%, popular value of 7%, and justice value of 7% and this animated series can be used as an alternative learning medium on the theme of saving living things class VI elementary school.